To what extent have learners with severe, profound and multiple learning difficulties been excluded from the policy and practice of inclusive education?. Issue 7 (6th June 2020) - Colley, Andrew
ABSTRACT: The article is a position paper on inclusive practice in education with respect to students with severe or profound and multiple learning difficulties (sld/pmld). It asks if children and young people with sld/pmld have been excluded from the policy and the practice of inclusive education. A review of the literature found that there is a research gap around inclusive education for learners with sld/pmld, and a review of historical and current practices indicated that this group of learners has indeed been excluded from both the policy and practice of inclusion in the United Kingdom with the use of curricula based on a mainstream linear and academic model reinforcing this exclusion. The study makes a theoretical and practical contribution to the continuing debate about inclusive education and will be of interest to teachers, parents, policy-makers and the learners themselves.